Strategi Pembelajaran Bahasa Arab Maharah Qira’ah di MTs 05 Kalikuning - Fatkurrohima, Ann Farid; Alwi, Itsnaini Muslimati (Lembaga Yasin AlSys, 2025)
Reading skills (maharah qira’ah) are fundamental competencies in Arabic language education, particularly at the junior secondary level in institutions such as Madrasah Tsanawiyah. This study addresses the challenges faced by MTs 05 Kalikuning, including low student engagement, monotonous teaching methods, and a lack of interactive learning media. The purpose of this research is to identify and develop innovative teaching strategies aimed at enhancing the effectiveness of Arabic language instruction, with a specific focus on reading skills. Employing a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings reveal that integrating communicative approaches, simple digital media, and group discussion methods significantly improves student participation and comprehension of Arabic texts. This study underscores the necessity for innovation in Arabic language teaching methodologies to meet contemporary educational demands. The implications suggest that educators should adopt more creative lesson designs that prioritize comprehension and active student involvement over rote memorization, ultimately contributing to improved language acquisition outcomes.